Externally-Controlled Systems for Immunotherapy: From Bench to Bedside - Tristán-Manzano, María; Justicia-Lirio, Pedro; Maldonado-Pérez, Noelia; Cortijo-Gutiérrez, Marina; Benabdellah, Karim; Martin, Francisco (Frontiers in Immunology, 2020)
Immunotherapy is a very promising therapeutic approach against cancer that is particularly effective when combined with gene therapy. Immunogene therapy approaches have led to the approval of 4 advanced therapy medicinal products (ATMPs) for the treatment of p53-deficient tumors (Gendicine and Imlygic), refractory acute lymphoblastic leukemia (Kymriah) and large B-Cell lymphomas (Yescarta). In spite of these remarkable successes, immunotherapy is still associated with severe side effects for CD19+ malignancies and is inefficient for solid tumors. Controlling transgene expression through an externally administered inductor is envisioned as a potent strategy to improve safety and efficacy of immunotherapy. The aim is to develop smart immunogene therapy-based-ATMPs, which can be controlled by the addition of innocuous drugs or agents, allowing the clinicians to manage the intensity and durability of the therapy. In the present manuscript, we will review the different inducible, versatile and externally controlled gene delivery systems that have been developed and their applications to the field of immunotherapy. We will highlight the advantages and disadvantages of each system and their potential applications in clinics